New Advances in Mechanisms, Mechanical Transmissions and Robotics: Proceedings of the Joint International Conference of the XII International Conference on Mechanisms and Mechanical Transmissions (MTM) and the XXIII International Conference on Robotics (Robotics '16) - Corves, Burkhard; Lovasz, Erwin-Christian; Hüsing, Mathias; Maniu, Inocentiu; Gruescu, Corina (Mechanisms and Machine Science, 2016)
This volume contains applications of mechanisms and transmissions in several modern technical fields such as mechatronics, biomechanics, machines, micromachines, robotics and apparatus.